Faktor-Faktor yang Mempengaruhi Status Gizi Balita di Wilayah Kerja Puskesmas Bakunase Kecamatan Kota Raja Pada Tahun 2023 - Nadia Polin; Rina Waty Sirait; Honey Ivon Ndoe (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Nutritional status is a condition that develops as a result of a balance between the food intake consumed and the amount of nutrients used for body metabolism. Toddlers are an important age group in children's growth and development both physically and mentally. Nutritional problems in toddlers can have several serious effects. Among other things, such as failure to develop physically, less than optimal growth and intelligence, and can even cause death in toddlers. The aim of this research was to determine the influence of knowledge, maternal education, parenting patterns and infectious diseases on nutritional status in the Bakunase health center working area. This type of research is an analytical survey with a research design using a cross sectional study approach. This research was conducted in the Bakunase Community Health Center work area in February 2024 – March 2024. The sample size in this study was 92 samples. The analysis used is univariate analysis and bivariate analysis. The type of statistical test uses the chi square test with a significance level of ɑ=0.05. The results of this study show that variables that have a relationship are maternal knowledge (p-value=0.001), maternal parenting style (p-value=0.000), infectious diseases (p-value=0.000). and which has no relationship with the nutritional status of toddlers, namely maternal education with a value (p-value 0.1000). It was concluded that maternal knowledge, parenting patterns, infectious diseases had an effect on nutritional status, while maternal education had no effect on nutritional status. For mothers who have toddlers, they should always pay attention to their child's nutritional intake.